2020
DOI: 10.1021/acsami.0c11402
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Structured Laser-Induced Graphene for Enhanced Boiling on Flexible Substrates

Abstract: Thermal management problems in high-power flexible electronics are exacerbated by the design complexity and requirement of stringent temperature control to prevent skin burns. Thus, effective heat dissipation methods applicable to flexible electronics on polymer substrates are an essential device design component. Accordingly, this study investigates the pool boiling heat transfer characteristics and potential enhancements, enabled by laser-induced graphene (LIG), which is both highly porous and bendable. Patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Moreover, LIG exhibits excellent mechanical flexibility. For example, Kong et al found the LIG strip still could hold good electrical properties even after 5000 cyclic bending tests [ 29 ]. Till now, various substrates, including wood, cloth, food, and paper, have been used to produce graphene layers [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LIG exhibits excellent mechanical flexibility. For example, Kong et al found the LIG strip still could hold good electrical properties even after 5000 cyclic bending tests [ 29 ]. Till now, various substrates, including wood, cloth, food, and paper, have been used to produce graphene layers [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other coating technologies involve atomic layer deposition, oxidation, , chemical vapor deposition, , electrophoretic deposition, etc. In addition, a wet/dry etching technique was used to fabricate micro pin fins, micro cavities, and nanowires, while a new emerging laser technique was also attempted to modify the boiling surfaces, obtaining micro pin fins and micro cavities . Pool boiling of various liquids was experimentally investigated on the surfaces mentioned above, including SES36, HFE-7200, , FC-72, ,,, n-pentane, and water, and on other surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a wet/dry etching technique was used to fabricate micro pin fins, micro cavities, and nanowires, while a new emerging laser technique was also attempted to modify the boiling surfaces, obtaining micro pin fins and micro cavities . Pool boiling of various liquids was experimentally investigated on the surfaces mentioned above, including SES36, HFE-7200, , FC-72, ,,, n-pentane, and water, and on other surfaces. It was found that the boiling performance was considerably enhanced, but micro/nanocomposite structures generally were more favorable than sole micro- or nanostructures concerning the heat transfer coefficient or the critical heat flux. ,, In terms of the enhancement mechanisms, heat transfer enhancement was usually attributed to several aspects, e.g., the increase in active nucleation site density, effective bubble dynamics, and enlarged heat transfer area, but the mechanisms of critical heat flux enhancement varied in various studies, e.g., liquid–vapor competition inside structures, wicking intensification, ,,, and liquid–vapor hydrodynamic instability .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pool boiling is a widely used cooling technique in high heat flux applications such as integrated microelectronic devices, nuclear reactors, and space equipment. , To meet the increasing heat dissipation demands, various surface patterns have been designed and investigated to enhance pool boiling heat transfer, such as micro-pin-fin, pillar, micro/nano tube, , nanowire, and microporous architecture . Results indicate that surface wettability has significant influence on pool boiling because it affects bubble behaviors and liquid wetting state on the heating surface. Previous studies have reported that hydrophobic surfaces promote early onset of nucleate boiling (ONB), although bubbles tend to stay on hydrophobic surfaces, which leads to lower critical heat flux (CHF). On the contrary, hydrophilic surfaces delay the CHF, but they need larger superheat to initiate nucleate boiling. ,, …”
Section: Introductionmentioning
confidence: 99%